Clinical, Endoscopic, and Histopathology Features of Esophageal Graft-vs-Host Disease. (18th July 2022) - Kamboj, Amrit K.; Agarwal, Siddharth; Yarlagadda, Manoj K.; Archila, Luisa Ricaurte; Hagen, Catherine E.; Katzka, David A.
Abstract : INTRODUCTION: To describe the clinical, endoscopic, and histopathology features of esophageal graft-vs-host disease (GVHD). Methods: Patients with biopsy-proven esophageal GVHD diagnosed at Mayo Clinic between 2000 and 2021 were included. Results: In 43 esophageal patients, other organ GVHD was present in 58% before and 86% at esophageal GVHD diagnosis. Esophageal specific symptoms were uncommon (dysphagia 26% and odynophagia/heartburn 5%). Esophagogastroduodenoscopy was abnormal in 72% patients demonstrating erosive esophagitis, ulceration, desquamation, or rings/furrows in a diffuse or focal pattern. DISCUSSION: There should be a low threshold for esophageal biopsies for GVHD because esophageal symptoms and endoscopic findings may be nonspecific or absent.